2014
DOI: 10.1016/j.livsci.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Water and concentrate intake, weight gain and duration of diarrhea in young suckling calves on different diets

Abstract: a b s t r a c tDiarrheic calves are fed with milk or milk replacer and oral rehydration solutions (ORS) to ensure energy and electrolyte supply. An easy and time-saving method is the preparation of ORS in milk. As milk-based ORS are hypertonic solutions administration of them may trigger thirst. Therefore, we hypothesized that restrictively fed calves receiving ORS prepared in milk had a higher water intake than restrictively and ad libitum fed calves receiving ORS prepared in water during diarrheic episodes.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
1
29
0
3
Order By: Relevance
“…Although water intake was not measured in the current study, this increase in visit duration may suggest an increase in the amount of water being consumed during each visit. Previous studies (Jenny et al, 1978;Wenge , 2014) found water intake to increase in diarrheic calves. Similar results have also been found in pigs, whereby water intake increased the day before overt clinical signs of an enteric disease were seen (Madsen and Kristensen, 2005).…”
Section: Discussionmentioning
confidence: 82%
“…Although water intake was not measured in the current study, this increase in visit duration may suggest an increase in the amount of water being consumed during each visit. Previous studies (Jenny et al, 1978;Wenge , 2014) found water intake to increase in diarrheic calves. Similar results have also been found in pigs, whereby water intake increased the day before overt clinical signs of an enteric disease were seen (Madsen and Kristensen, 2005).…”
Section: Discussionmentioning
confidence: 82%
“…Ideally, ORT should be administered in addition to milk feeding at different times of day to provide additional fluid as well as the electrolytes required. When ORT is provided in milk replacer, it is essential that ad libitum access to water is also available (Kirchner and others 2014, Wenge and others 2014). …”
Section: Oral Rehydration Therapymentioning
confidence: 99%
“…Isso ocorre por que estas soluções provocam sensação de sede, incrementando o consumo de água voluntário. No entanto, este tipo de tratamento demanda o fornecimento de água ad libitum de modo de evitar situações de hipernatremia (WENGE et al, 2014).…”
Section: Soluções Eletrolíticas Orais Hiperosmóticas (>312 Mosmunclassified
“…As soluções eletrolíticas fornecidas junto com a dieta líquida com disponibilidade de água ad libitum, são um método simples de reidratação para animais com quadro de diarreia, que simplificam o trabalho do produtor (WENGE et al, 2014;BACHMANN et al, 2012;GOODELL et al, 2012). Em contrapartida, outras soluções orais eletrolíticas devem ser fornecidas num horário afastado daquele utilizado para o aleitamento dos animais de modo que não seja comprometida a formação do coágulo no abomaso, o que significa trabalho extra para o produtor (SMITH e BERCHTOLD, 2014).…”
Section: Soluções Eletrolíticas Orais Hiperosmóticas (>312 Mosmunclassified
See 1 more Smart Citation